Understanding undergraduate nursing students’ knowledge of, and attitudes to, prenatal genetic screening in Malaysia: A preliminary study - Soon, Lean Keng; Pricilia Dew Maria, Stephen; Lai, Sue Yi (International Journal of Advanced Nursing Studies, 2013)
Background: Nursing students must be able to ensure that patients understand important health screening information. However, studies have reported a deficit in nursing students’ knowledge of genetics and genetic disorders. Aim: The purpose of this study was to investigate nursing students’ knowledge of, and attitudes to prenatal genetic screening. Methods: A descriptive, cross-sectional survey was conducted with final year undergraduate nursing students recruited from a tertiary teaching hospital in Kelantan, Malaysia. Thirty-four of the 37 students returned a self-administered questionnaire (response rate=97%) that assessed knowledge of, and attitudes to, prenatal genetic screening. Findings: The majority of the respondents demonstrated an adequate level of knowledge regarding prenatal genetic screening (65%), and 62% were more supportive than others of screening. Approximately one third (35%) had limited knowledge. Simple linear regression analysis uncovered a significant linear relationship between the attitude score and the knowledge score (R2=0.48, P<0.05, 95% confidence interval). Conclusions: These findings suggest the need to improve and upgrade the nursing education strategy concerning genetics. The deficit in nursing students’ knowledge of prenatal genetic screening may result in inappropriate counselling, health teaching and referrals, which can have serious repercussions.